2021
DOI: 10.1051/e3sconf/202123603033
|View full text |Cite
|
Sign up to set email alerts
|

Research on Interactive Soundscape Design for Urban Landscape

Abstract: This paper intends to discuss the concept and design elements and methods of the interactive soundscape for urban landscape through the analysis on the influence relationship of components of a soundscape for urban landscape. With the analysis on the composition of the acoustic environment for urban landscape as the starting point, it finds out the implicit relationship of components of the acoustic environment, introduces the concept of interactive design, proposes the concept and components of the interactiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…In the model, water was rejected as having no influence on the assessment of the parks as perceived by respondents. Other research confirmed the importance of water in the positive perception of park space, and, additionally, water can mask unpleasant sounds [22,29]. The significance of water sounds in city design has gained increasing attention due to the growing interest in innovative hydro-sounds and their positive impact on the health and well-being of urban residents [11,30].…”
Section: The Impact Of Different Types Of Sound In Overall Perception...mentioning
confidence: 91%
See 1 more Smart Citation
“…In the model, water was rejected as having no influence on the assessment of the parks as perceived by respondents. Other research confirmed the importance of water in the positive perception of park space, and, additionally, water can mask unpleasant sounds [22,29]. The significance of water sounds in city design has gained increasing attention due to the growing interest in innovative hydro-sounds and their positive impact on the health and well-being of urban residents [11,30].…”
Section: The Impact Of Different Types Of Sound In Overall Perception...mentioning
confidence: 91%
“…Natural: sounds of birds, insects, wind, and water. Some of them clearly presented the results in a cluster, which was an inspiration to create a comparative analysis cluster for each study site [8,21,22] (Supplementary Materials S2).…”
Section: Surveymentioning
confidence: 99%
“…The starting point in soundscape design is the identification of the existing unfavourable acoustic qualities and the pleasant sounds on the site and taking account of the possibilities to abolish or mask unwanted sounds [11,14,15,16,17]. Finally, the new, desirable sound identity of the place needs to be determined [3].…”
Section: ) Ultimate Methods In Soundscape Designmentioning
confidence: 99%